2021
DOI: 10.25259/sni_53_2021
|View full text |Cite
|
Sign up to set email alerts
|

The historic evolution of intracranial pressure and cerebrospinal fluid pulse pressure concepts: Two centuries of challenges

Abstract: Background: There is a consensus on the importance of monitoring intracranial pressure (ICP) during neurosurgery, and this monitoring reduces mortality during procedures. Current knowledge of ICP and cerebrospinal fluid pulse pressure has been built thanks to more than two centuries of research on brain dynamics. Methods: Articles and books were selected using the descriptors “ICP,” “cerebrospinal fluid pulse,” “monitoring,” “Monro-Kellie doctrine,” and “ICP waveform” in electronic databases PubMed, Lilacs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…[16] and Lang tt et al [23], by means of invasive ICP measurement, observed the relation between intracranial volume and ICP variations [24], whereas Nucci et al [20] con rmed that changes in ICPW followed ICP variations; in particular, elevation of the second ICP peak was related to impaired ICC, although quantitative relations between ICPW peaks were not demonstrated in that study. Kazimierska et al [25] performed intracranial elastance assessment by means of infusion test in normal pressure hydrocephalus patients and compared three techniques, including changes in P1 and P2 amplitudes, indicating that the ratio obtained from these peaks has good correlation with the intracranial volumetric manipulation.…”
Section: Discussionmentioning
confidence: 82%
“…[16] and Lang tt et al [23], by means of invasive ICP measurement, observed the relation between intracranial volume and ICP variations [24], whereas Nucci et al [20] con rmed that changes in ICPW followed ICP variations; in particular, elevation of the second ICP peak was related to impaired ICC, although quantitative relations between ICPW peaks were not demonstrated in that study. Kazimierska et al [25] performed intracranial elastance assessment by means of infusion test in normal pressure hydrocephalus patients and compared three techniques, including changes in P1 and P2 amplitudes, indicating that the ratio obtained from these peaks has good correlation with the intracranial volumetric manipulation.…”
Section: Discussionmentioning
confidence: 82%
“…2 ) which significantly damped the amplitude of the cardiac CSF pulsations (Fig. 2 A,C) as it does in humans 31 . With the alligator in the head-down position, a slight shift in the peritoneal viscera would have raised intrathoracic pressure, which, when combined with the increase in central venous pressure, would have damped the ventilatory pulsations 32 .…”
Section: Discussionmentioning
confidence: 68%
“…Professor Mascarenhas questioned the validity of the Monro-Kellie doctrine, which stated that the skull is nonexpandable [ 1 , 2 ], despite the fact that even diamonds expand when subjected to pressure. This inquiry drove him to make the first discovery of a linear correlation between cranial microexpansion and changes in ICP [ 3 ].…”
Section: The Historic Narrativementioning
confidence: 99%